Biography of an Industrial Landscape : Carlsberg's Urban Spaces Retold - Riesto, Svava (Book collections on Project MUSE.)
Europe has been urbanised for so long that there are few undeveloped sites available for new development. That has led cities to turn to abandoned former industrial sites, a decision that raises a number of questions about preservation and reuse. 'Biography of an Industrial Landscape' addresses how industrial sites are reworked in the present and shows what deeper questions about values and cultural imaginaries lie behind our decisions. This book is based on a deep case study of the Carlsberg brewery site in Copenhagen - one of the most discussed European urban redevelopment projects at the turn of the 21st century. Landscape biography, Svava Riesto shows here, can be a useful scope for deepening our knowledge about an aspect of industrial sites that often escapes attention; its open spaces. The study reappraises the industrial open spaces of Carlsberg and unfolds how they have emerged by interrelated transformations ranging from yeasting, transportation networks to daily walks and changing aesthetics. Further, the book unravels how contemporary urban redevelopment is linked to cultural imaginaries and inherited myths that influence how we think about what is possible.